Development of Brake System E-Job Sheet Learning Media on Shasis Maintenance and Light Vehicle Power Transfer Courses at SMK Muhammadiyah Semin - Choiril Ahmad Azis Azis; Suparmin; samsul hadi (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2024)
Development of Brake System E-Job Sheet Learning Media on Shasis Maintenance and Light Vehicle Power Transfer Courses at SMK Muhammadiyah Semin Abstract: The purpose of this study is to develop learning media in the subjects of chassis maintenance and light vehicle power transfer at SMK Muhammdiyah Semin in the form of: (1) Electronic job-sheet on conventional brake system competence. (2) see the feasibility level of the e-job sheet that has been developed at SMK Muhammadiyah Semin. This study uses the Research and Development (R&D) method, the development model using the Four-D by Thiagaradjan. The Four-D uses four methods, namely Definen, Design, Develop, Disseminate. The results of the analysis and discussion state: 1) This development obtains learning resources that are in accordance with the contents of the syllabus, including e-job sheet the brake system2) the feasibility level on the e-job sheet can be seen in the results of research from experts and the results of student responses. Material expert validation covers aspects of the feasibility of content, linguistics, presentation, and usefulness having an average of 90.8% in the